2019
DOI: 10.1186/s12984-019-0530-z
|View full text |Cite
|
Sign up to set email alerts
|

An augmented reality approach for ADL support in Alzheimer’s disease: a crossover trial

Abstract: Background Dementia of the Alzheimer’s type can impair the performance of activities of daily living and therefore severely impact independent living. Assistive technologies can support such patients when carrying out daily tasks. Methods In this crossover study, we used an augmented reality approach using a Microsoft HoloLens to support patients in a tea making task. During task execution, subjects received three-dimensional dynamic holograms of the sub-steps necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 16 publications
1
43
0
3
Order By: Relevance
“…Six records were excluded because they did not report any outcomes that were directly related to social participation or self-management [ 61 , 62 , 63 , 64 , 65 , 66 ]. Four records reported on BADLs only [ 67 , 68 , 69 , 70 ]. Three studies were excluded because although participants with some form of cognitive impairment were included in the study, the outcomes were not reported separately from outcomes from those who were either cognitively healthy or had other pathologies [ 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six records were excluded because they did not report any outcomes that were directly related to social participation or self-management [ 61 , 62 , 63 , 64 , 65 , 66 ]. Four records reported on BADLs only [ 67 , 68 , 69 , 70 ]. Three studies were excluded because although participants with some form of cognitive impairment were included in the study, the outcomes were not reported separately from outcomes from those who were either cognitively healthy or had other pathologies [ 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Along with an aging population, potential users will be between 60 and 80 years old, which is accompanied by different forms of disabilities (ie, impaired vision, hearing, or cognitive function) that can complicate use. However, mixed reality seems to be an accessible and feasible tool in the elderly, as highlighted by Rohrbach et al [ 30 ] in patients with Alzheimer disease. Since patients with Alzheimer disease comprise a complex patient group, it is feasible to assume that patients with no cognitive impairments might also benefit from mixed reality apps.…”
Section: Discussionmentioning
confidence: 99%
“…The participants in the ARGroup outperformed those in the NoARGroup in memorizing objects and their positions [ 17 ]. Rohrbach et al used AR to provide activities of daily living support for patients with AD [ 18 ]. In their crossover study, a head-mounted Microsoft HoloLens was used to verify the feasibility and usability of AR that supported patients with AD in tea brewing activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The surmised reason was that the AR application only provided seven-step prompts and lacked more detail, which confused the patients. Therefore, the provision of more detailed content is crucial to improving the completion rate of patients [ 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%